Aarhus Kunstmuseum : Katalog over Malerisamlingen 1854-1983. (Aarhus : Aarhus Kunstmuseum, 1984)
Aagaard, Carl Frederik ; Abildgaard, Nicolai Abraham ; Abrahamsson, Anette ; Achen, Gerog ; Adler Petersen, Lene ; Agersnap, Hans Jacob Soltoft ; Agersnap, Hans Mortensen ; Agger, Knud ; Alfelt, Else ; Als, Peder ; Anastasi, August Paul Charles ; Ancher, Anna ; Ancher, Michael ; Andersen, Mognes ; Bache, Otto ; Bendtsen, Folmer ; Bendz, Wilhelm ; Bentzen, Axel ; Bergsoe, Flemming ; Bernhard-Frederiksen, Aage ; Besnard, Paul Albert ; Bille, Ejler ; Bissen, Rudolf ; Bjerke-Petersen, Vilhelm ; Bjerre, Niels ; Bjorklund, Poul ; Blache, Christian ; Bloch, Carl ; Blunck, Ditlev Conrad ; Boberg, Jörgen ; Bouquet, Michel ; Bovin, Karl ; Brandes, Peter ; Brandt, Viggo ; Brasen, Hans Ole ; Brendekilde, Hans Andersen ; Brockdorff, Victor ; Carlsson, Harry ; Carstensen, Ebba ; Cavé, Jules Curille ; Christensen, Godfred ; Christensen, John ; Christensen, John Sparre ; Christensen, Kay ; Christensen, Kirsten ; Christiansen, Poul Simon ; Christofferson, Frede ; Ciceri, Eugène ; Clausen, Franziska ; Cour, Janus la ; Dahl, Johan Christian ; Dahlin, Dorte ; Dall, Hans ; Dalsgaard, Christen ; Daugaard, Niels Christian ; Dewasne, Jean ; Deyrolle, Jean ; Diedrichsen, Ulla ; Didier, Jules ; Didier-Pouget, William ; Dorph, Anton ; Dorph, Bertha ; Dreyer, Dankvart ; Duart, Angel ; Duarté, José ; Dybris, Freddie ; Eckersberg, Christoffer Wilhelm ; Ejstrup, Kaj ; Ekelund, Poul ; Elgaard, Soren ; Engelund, Svend ; Van Everdingen, Allart ; Exner, Julius ; Find, Ludvig ; Fischer, August ; Flachner, Ferdinand Wolfgang ; Fonnesbech-Sandberg, Elna ; Foss, Harald ; Fossi ; Frandsen, Erik A. ; Freddie, Wilhelm ; Fredslund Andersen, Aage ; Friis, Hans ; Fritz, Andreas ; Führer, Kai ; Gebauer, Christian David ; Geertsen, Ib ; Gernes, Paul ; Gertner, Johan Vilhelm ; Giersing, Harald ; etc.
boek